EVALUATION OF THE DIELECTRIC AND SEMI-CONDUCTOR COATING EFFECTS ON THE MICROWAVE ABSORPTION PROPERTIES OF METALS - Yahaya, Aliyu; Ali, Mutari Hajara (FUDMA Journal of Sciences, 2025)
This research evaluated the effects of dielectric and semiconductor coatings on the microwave absorption properties of three metals: aluminum, copper, and zinc. Using COMSOL Multiphysics software, simulations were performed to analyze the interaction of microwave radiation with these metals, both in their uncoated form and when coated with dielectric and semiconductor materials of varying thicknesses. The study involved creating geometric models, applying material properties, and conducting frequency domain analyses to determine absorption characteristics. The results revealed that coating thickness played a critical role in improving microwave absorption. Optimal thicknesses for dielectric coatings reduced reflectivity and provided impedance matching layers that facilitated greater microwave penetration. Semiconductor coatings further increased absorption due to their tunable conductivity and effective loss mechanisms, which efficiently converted microwave energy into heat. Aluminum and copper exhibited low absorption in their uncoated form due to high electrical conductivity and reflectivity, while zinc displayed moderate absorption. When coated, all three metals demonstrated significantly enhanced absorption, with the impact varying based on coating type and thickness. These findings have significant implications for applications in electromagnetic interference (EMI) shielding, microwave devices, and materials science. By understanding the influence of coating thickness on microwave absorption, this study provides insights for optimizing material designs and tailoring coating parameters to enhance performance for shielding technologies and microwave absorption applications. This research highlights the potential of coatings to overcome the limitations of metals and improve their functionality in diverse technological and industrial fields.